Hospital acquired Clostridium difficile infection in pediatric wards: a retrospective case-control study - ÜLGER, NURVER; YAKUT, NURHAYAT (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
Background: Clostridium difficile is a major cause of antibiotic-associated diarrhea and frequently results in health-care-associated infections. The aim of this study was to determine the incidence and potential risk factors for C. difficile infection (CDI) in hospitalized children who developed diarrhea. A retrospective study was performed at a university hospital in Istanbul over a three-year period (2012-2014). Results: During the study period 12,196 children were hospitalized, among them 986 (8 %) children with diarrhea were investigated for CDI and 100 (0.8 %) children were diagnosed with CDI. The incidence of CDI in hospitalized children was 4/1000, 9/1000 and 9/1000 patients per year in year 2012, 2013 and 2014, respectively (p = 0.008, p < 0.01). The mean age of children with CDI (2.6 +/- 2.6 months) was lower than children without CDI (57.5 +/- 63.5 months) [p = 0.001]. In the multivariate analysis, the presence of underlying chronic diseases [presence of malnutrition (OR 7, 95 % CI 1.33-36.7, p = 0.021), presence of solid organ tumors (OR 6, 95 % CI 2.4-15.7, p < 0.00), presence of congenital heart diseases (OR 4.6, 95 % CI 1.13-18.7, p = 0.03), hospitalization in PICU (OR 15.6, 95 % CI 3.2-75.8, p = 0.001) and hospitalization in hematology and oncology ward (OR 7.8, 95 % CI 2-29.9, p = 0.002)] were found to be independent risk factors for CDI. Conclusion: This is the first description of the incidence and associated risk factors of CDI in Turkish children. One of the most important risk factor was prior antibiotic exposure which emphasizes the importance of antibiotic stewardship programs.
Keywords: C. difficile infection; Hospitalized children; Antibiotic use; UNITED-STATES; CHILDREN; INFANTS; RISK; DIARRHEA; DISEASE; BURDEN; STRAIN